‘Coming out’ : experiences of Singaporean gay men across different ethno-religious backgrounds - Lau, Paul (2015)
This study aims to explore the ways in which Singaporean gay men negotiate their ‘coming out’ process. Through in-depth interviews, influences of religion and ‘coming out’ audience on the homosexual identity development were delineated. The respondents consisted of predominantly Christians and Muslims so as to draw comparisons amongst gay men from these two religious groups. The interview data collected showed that: (1) Christian respondents could reconcile their sexual identities with Christianity after joining Free Community Church (FCC), (2) Muslim respondents could not reconcile their sexual identities with Islam because of the parents’ denial and (3) Most respondents coped with stigmatizations through homonormativity.